2003
DOI: 10.1128/iai.71.12.6986-6994.2003
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Wolbachia from Brugia pahangi Is Closely Linked to Worm Death and Fecundity but Does Not Result in Altered Lymphatic Lesion Formation in Mongolian Gerbils ( Meriones unguiculatus )

Abstract: Approximately 30 years ago, researchers reported intracellular bacteria in filarial nematodes. These bacteria are relatives of the arthropod symbiont Wolbachia and occur in many filarial nematodes, including Brugia pahangi and Brugia malayi. Wolbachia bacteria have been implicated in a variety of roles, including filaria development and fecundity and the pathogenesis of lymphatic lesions associated with filarial infections. However, the role of the bacteria in worm biology or filarial disease is still not clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 51 publications
3
24
0
1
Order By: Relevance
“…The present study showed that jirds infected with normal B. malayi L3 did not develop antibodies to Wolbachia wsp until the onset of microfilarial patency. This result was consistent with results reported in studies of B. pahangi (Chirgwin et al 2003). Wolbachia densities in worms appear to multiply Jirds vaccinated with irradiated L3 were largely immune to challenge infections, as expected.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that jirds infected with normal B. malayi L3 did not develop antibodies to Wolbachia wsp until the onset of microfilarial patency. This result was consistent with results reported in studies of B. pahangi (Chirgwin et al 2003). Wolbachia densities in worms appear to multiply Jirds vaccinated with irradiated L3 were largely immune to challenge infections, as expected.…”
Section: Discussionsupporting
confidence: 92%
“…This data supports the earlier reports of no incidental effect of antibiotic on natural filarial infections by conventional periods of antibiotic therapy (3 -5 days) and thus, there is a substantial requirement of longer periods of treatment (Bandi et al 2001). Reports from other groups have demonstrated clearance of bacteria after 76 days continuous treatment but the effect on worm recovery could be seen only if treatment was continued for at least 86 -100 days (Chirgwin et al 2003). Therefore, the treatment schedule in the present study was extended upto 90 and 120 days to ensure complete elimination of endobacteria from the worms that in turn ensure elimination of filarial parasite.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of complete pathways for nucleotide and heme biosynthesis in Wolbachia and their partial absence in the filarial parasites, coupled with the observation of a loss of viability and reproductive capacity of the filarial organisms following elimination of Wolbachia by antibiotics (42)(43)(44), suggest that the endosymbiont provides crucial signals and pathway components critical for parasite survival. Interestingly, all the members of the heme biosynthetic pathway, except for the ferrochelatase (Wbm0719) and the protoporphyrinogen oxidase, which is absent from the Wolbachia genome, were detected in the present proteomic analysis.…”
Section: Resultsmentioning
confidence: 99%